Analysis of Staphylococcus aureus and Escherichia Coli and its Susceptibility to Antibiotic in Catheter-Associated Urinary Tract Infection Patients at Hospital in Province of West Nusa Tenggara - BaiqIsti Hijriani; ManikRetno Wahyunitisari; Agung Dwi Wahyu Widodo (Institute of Medico-legal Publications Pvt Ltd, 2022)
Objective – This study aimed to analyze the proportion of Staphylococcus aureus and Escherichia colifrom urine samples of catheter-associated urinary tract infections (CA-UTI) patients at the GeneralHospital at Province of West Nusa Tenggara. Also measured the pattern of sensitivity to severalantibiotics.Methods –This study is a descriptive observational with a cross-sectional approach. A total of 60 sampleswere used in this study. Bacterial identification was carried out according to standard bacteriologicalculture techniques. Furthermore, the antibiotic sensitivity test following the Kirby-Bauer disc diffusionmethod using several antibiotics, including amoxycillin (AMP), ciprofloxacin (CIP), ceftriaxone(CRO), and sulphamethoxazole trimethoprim (SXT).Results –The results showed that bacteria causing CA-UTI were Staphylococcus aureus (43.33%),Escherichia coli (21.67%), Staphylococcus epidermidis (10%), Proteus mirabilis (6.67%), Enterobacteraerogenes (6.67%), Serratica marcescens (5%), Klebsiella sp (3.33%), and Pseudomonas sp (3.33%).The antibiotic susceptibility test found that 4.58%, 11.25%, 9.16%, and 3% of bacteria were resistant toamoxycillin, ceftriaxone, ciprofloxacin, and sulphamethoxazole trimethoprim, respectively.Conclusion –Staphylococcus aureus and Escherichia coli were the most gram-positive and gramnegativebacteria causing CA-UTI, respectively. The most resistant antibiotic was ciprofloxacin, andthe most sensitive antibiotic is sulphamethoxazole trimethoprim.